Destination Atmosphere and Destination Branding: As an Effort to Promote Tourism in Banten - Liza Mumtazah Damarwulan (Budapest International Research and Critics University, 2021)
This study departs from the problem that there are still many tourist attractions or tourist destinations in Indonesia that have not been exposed and need a touch of promotion in order to encourage the level of tourist visits. One of them is by using destination branding and destination atmosphere as an effort to attract the interest of visiting the community and in the end the community can make a decision to visit the destination tourist location. This study aims to further examine the destination branding and destination atmosphere as an effort to promote tourism in Banten. This type of research is quantitative research. The data collection technique in this study was conducted by survey techniques using a questionnaire as a research instrument, with a purposive sampling technique. Data analysis used (SEM) analysis techniques and AMOS program analysis tools. The results show that there is a positive and significant influence between social media and visiting interest, destination branding has a positive and significant effect between visiting interest, destination atmosphere has a positive and significant effect between g and visiting interest, there is a positive and significant influence between destinations. Branding with visiting decisions, there is no positive and significant influence between destination atmosphere and visiting decisions, and there is a positive and significant influence between interest in visiting and visiting decisions.